Perbandingan Status Gizi Balita, Data Susenas 2005 Berdasarkan Rujukan Harvard, NCHS, CDC dan Standar WHO - Nadiyah, Nadiyah; Jus'at, Idrus; Zulfianto, Nils Aria; Atmarita, Atmarita (Lembaga Penerbitan Unversitas Esa Unggul, 2010)
AbstractAccording to the comparison of WHO curve standards in 2005 with international standards earlier, they said that the prevalence of infants who are underweight and age in the first half-year period will be increased and the prevalence of underweight children above the age of 6 months will be decreased. The aims of this study is to determine the proportion of malnutrition among children under five years between four reference standards and differences of standards (Havard, NCHS, CDC, and WHO Standards) and large of deviation by previous references to the new standards. This analysis used survey design along with comparative study. The sample of this study is children with aged 0-59 months from data SUSENAS 2005 (93.0). The data was collected such as gender, date of birth, date of weighing, and body weight. The results shows the proportion of underweight children underfive year among four references and standards is different in particular ages. In the analysis of sensitivity and specificity shows that the reference category of nutritional deviation value from CDC is lower (2.15% for males and 1.89% for females) than the other standards. The deviation values of Harvard is 8.41% for males and 4.08% for females. The deviation values of NCHS is 4.65% for males and 21.4% for females. TheÂ standard instruction of WHO as description of growth â€œwhat should beâ€ is the best food for infants aged 0-6 months is only breast milk or we called exclusive breastfeeding and the further we should give additional foods after 6 months by continuing give the breastfeeding until 24 months.Keywords: children under five year, nutritional status, WHO standardÂ AbstrakPada tahun 2005, WHO mengeluarkan standar internasional baru yang disebut Standar WHO 2005. Oleh WHO, perbandingan kurva standar WHO 2005 dengan standar-standar internasional sebelumnya telah digambarkan dalam grafik dan dikatakan bahwa dengan menggunakan standar WHO, prevalensi bayi yang mengalami kekurangan berat badan dan usianya dalam periode setengah tahun pertama akan meningkat dan prevalensi anak yang berat badannya kurang diatas umur 6 bulan akan menurun. Analisis ini bertujuan untuk mengetahui apakah proprosi balita gizi kurang antara keempat rujukan dan standar (rujukan Harvard, NCHS, CDC dan standar WHO) berbeda dan seberapa besar penyimpangan oleh rujukan-rujukan sebelumnya terhadap standar terbaru. Analisis ini menggunakan pendekatan survei dengan jenis studi komparatif. Sampel adalah kelompok balita usia 0-59 bulan berasal dari data Susenas 2005, sebanyak 93044 balita. Data yang dikumpulkan adalah data jenis kelamin, tanggal lahir, tanggal penimbangan, dan berat badan. Hasil uji beda proporsi menyatakan bahwa proporsi balita gizi kurang antara keempat rujukan dan standar saling berlainan pada umur-umur tertentu. Pada analisis sensitifitas dan spesifisitas tampak bahwa rujukan yang penyimpangan pengkategorian gizi kurangnya paling kecil adalah rujukan CDC (2.15% pada laki-laki dan 1.89% pada perempuan). Penyimpangan pada rujukan Harvard sebesar 8.41% untuk laki-laki dan 4.08% untuk perempuan. Penyimpangan pada rujukan NCHS sebesar 4.65% untuk laki-laki dan 4.21% untuk perempuan. Pesan standar WHO sebagai gambaran pertumbuhan â€œwhat should beâ€ adalah bahwa makanan yang terbaik bagi anak usia 0-6 bulan adalah ASI saja atau disebut ASI eksklusif dan selanjutnya diberikan makanan tambahan setelah usia 6 bulan seiring ASI tetap diteruskan sampai umur 24 bulan.Kata kunci: balita, status gizi, standar WHO